Improving Feed Quality Through the Addition of Mangrove Fruit (Sonneratia alba) on Indigofera (Indigofera zollingeriana) - Elihasridas; Roni Pazla; Zaitul Ikhlas; Gusri Yanti; Imana Martaguri; Yelly Fitri; Rani Winardi Wulan Sari (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
This study investigated the effects of incorporating tannin-rich mangrove fruit (Sonneratia alba) into Indigofera zollingeriana-based rations on in vitro digestibility and rumen fermentation characteristics. Using a completely randomized design with four treatments (0%, 3%, 6%, and 9% S. alba) and four replicates, we evaluated dry matter digestibility (DMD), organic matter digestibility (OMD), crude protein digestibility (CPD), crude fiber digestibility (CFD), crude fat digestibility, nitrogen-free extract (NFE), rumen pH, volatile fatty acids (VFA), and ammonia (NH₃) concentrations. Results revealed that moderate tannin inclusion (6%) improved CPD and nutrient protection without significantly impairing DMD or OMD. However, higher inclusion (9%) significantly reduced CFD, crude fat digestibility, NFE, VFA, and NH₃ concentrations (P<0.05 or P<0.01), indicating suppressed microbial activity. These findings suggest that while S. alba tannins can effectively reduce ruminal protein degradation and modulate fermentation, excessive inclusion negatively impacts overall feed digestibility. The optimal inclusion rate was identified at 6%, balancing protein protection and fermentation efficiency. This study supports the strategic use of plant-based tannins as a feed additive to enhance protein utilization and reduce nitrogen losses in ruminant diets.